A "dual-key-and-lock" ratiometric fluorescent probe with biocompatibility and selectivity for imaging vicinal dithiol proteins. Issue 13 (25th January 2023) - Zou, Guang-Yue; Wen, Yun; Bi, Fan; Chen, Shuai; Yu, Yong-Liang; Wang, Jian-Hua
Abstract : A ratiometric fluorescent probe based on a "dual-key-and-lock" design was reported for the imaging of vicinal dithiol proteins in living cells. Abstract : TMR-TPE, a ratiometric fluorescent probe, was reported for the imaging of vicinal dithiol proteins (VDPs) in living cells. Profiting from the "dual-key-and-lock" design, TMR-TPE solves the toxicity problem of VDP probes (98% cell viability at 50 μM) and avoids the interference of small thiols (up to 10 mM GSH). The change of VDPs during drug-induced liver injury was monitored for the first time using TMR-TPE.